Clinical manifestation and laboratory findings as predictive factors for dengue mortality in Kota Bharu - Seng, Liu Yeo (2017)
Background: Dengue fever is an endemic disease in Malaysia. Changing of time made the classical clinical manifestation of dengue fever become vary and present a challenge in diagnosing and managing the patients. Warning signs and laboratory changes as describes in the WHO dengue guidelines 2009 are not usually present in every patient. We aim to identify the clinical manifestation and laboratory findings among the confirmed adults dengue-associated mortality patients in Kota Bharu Kelantan Malaysia. Methods: We conducted a case control study in all confirmed dengue death patients in Kota Bharu from January of 2005 till December 2015. All adult death patients were included and control was by computer-generated randomization. Four controls were chosen for every dengue-associated death case. Data were analysed by simple and multiple logistic regression. Results: Of 25 deaths, median age was 42 (SD ±14.5) years old. Male gender comprised of 56% and comorbidities existed in 60% of the cases. Majority of patients sought treatment at the average of day 5 of fever. The warning sign that most patients had were nausea/ vomiting while the least was mucosal bleed. Laboratory abnormalities on admission included leucopenia (40%), leucocytosis (16%), raised urea (28%) and creatinine (36%). 80% of the dengue-associated mortality had thrombocytopenia during presentation with mean of 74.2 x 103(SD ±62.61). Multiple logistic regression analysis showed two clinical manifestations were negatively associated with dengue-associated mortality – vomiting/nausea (adj. OR 0.13, 95% CI 0.02-0.76) and headache (adj.OR0.15, 95% CI 0.03-0.86). Laboratory findings that were associated with dengueassociated mortality were first TWC (adj. OR 1.82, 95% CI 1.08-3.05), second TWC (adj. OR 1.54, 95% CI 1.15-2.07), second platelet (adj. OR 0.97, 95% CI 0.95-0.99), urea (adj. OR 2.35, 95% CI 1.43-3.85) and creatinine (adj. OR 0.98, 95% CI 0.97-1.00). Conclusions: Dengue patients with vomiting/nausea and headache were the clinical manifestations of lower chance of having dengue-associated mortality. Laboratory findings of increasing in total white count and urea, reducing in platelet and creatinine were more likely to associate with dengue-associated mortality. Early detection of clinical deterioration and prompt treatment is the main key of prevention of death.